Pharmacotherapy of Alzheimer’s Disease: Seeking Clarity in a Time of Uncertainty - Husna Ibrahim, Nurul; Yahaya, Mohamad Fairuz; Mohamed, Wael; Teoh, Seong Lin; Hui, Chua Kien; Kumar, Jaya (Frontiers in Pharmacology, 2020)
Alzheimer’s disease (AD) is recognized as a major health hazard that mostly affects people older than 60 years. AD is one of the biggest medical, economic and social concerns to the patients and their caregivers. AD is ranked as the 5th leading cause of global deaths in 2016 by World Health Organization (WHO). Many drugs targeting the production, aggregation and clearance of Aβ plaques failed to give any conclusive clinical outcomes. This mainly stems from the fact that AD is not a disease attributed to a single-gene mutation. Two hallmarks of AD, Aβ plaques and neurofibrillary tangles (NFTs) can simultaneously induce other AD etiologies where every pathway is a loop of consequential events. Therefore, the focus of recent AD research has shifted to exploring other etiologies such as neuroinflammation and central hyperexcitability. Neuroinflammation results from the hyperactivation of microglia and astrocytes that release pro-inflammatory cytokines due to the neurological insults caused by Aβ plaques and NFTs, eventually leading to synaptic dysfunction and neuronal death. This review will report the failures and side effects of many anti-Aβ drugs. In addition, emerging treatments targeting neuroinflammation in AD such as nonsteroidal anti-inflammatory drugs (NSAIDs) and receptor-interacting serine/threonine protein kinase 1 (RIPK1) that restore calcium (Ca2+) dyshomeostasis and microglia physiological function in clearing Aβ plaques, respectively, will be deliberately discussed. Besides, other novel pharmacotherapy strategies in treating AD, including disease-modifying agents (DMTs), repurposing of medications used to treat non-AD illnesses and multi target-directed ligands (MTDLs) also are reviewed. These approaches open new doors to the development of AD therapy, especially combination therapy that can cater for several targets simultaneously, hence, effectively slowing or stopping AD.